Komputerowe wspomaganie zarządzania wiedzą w projektach informatycznych - Wojtkiewicz-Wydra, Ewa; Wójtowicz, Radosław (Computer-Supported Knowledge Management in IT-Projects, 2005)
The article contains the introduction to problem of technological aspect of knowledge management in IT-projects. In the first part of the article is presenting short description character of knowledge management with reference to IT-projects. In this framework authors presented definitions and they analyzed influence specificity undertakings to knowledge management in their space. The second part it is first of all survey available computer technology in point of view their usefulness and importance in knowledge management and general analysis of space which are actively to aid by mentioned technologies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 324-332